The effect of dapagliflozin on clinical, metabolic and renal parameters in type 2 diabetic patient in University of Malaya Medical Centre: A single centre experience / Ho Hee Kheen - Ho , Hee Kheen (2017)
As Asian patients with type 2 diabetes mellitus (T2DM) have significant beta cell dysfunction and increased visceral adiposity, we hypothesize that sodium glucose cotransporter inhibitors which acts independent from insulin dependent mechanisms, are effective in a multi ethnic T2DM population in real-world setting. A retrospective T2DM cohort (N=ll 0) treated with dapagliflozin for months was identified from the electronic pharmacy database. Estimated glomerular filtration rate (eGFR) was calculated using CKD-EPI 2009 equation. Missing laboratory values were imputed utilizing the "last observation-carried-forward" method. The 6- and 12-month postinterventional differences in biochemical profiles were examined using linear mixed-effects model or Friedman test. The mean age [±standard deviation] and disease duration [± standard deviation] were 56.2±9.5 and 14.8±8.0 years, respectively; mean HbA1c [±S.D.] was 70±14 rnmoVmol (8.6± 1.3%), 43.6% were men, and 22.7% had existing cardiovascular disease. The proportions of participants based on ethnicity were Malay 31.8%, Chinese 29 .I% and Indian 33 .6%. At 12 months, there was a significant decline in HbA1c (Mdndifference -10 mmol/mol [- 0.9%], 95% CI -13 to -8 mmoVmol [1.2 to -0.7%], P<O.OOI), systolic blood pressure (SBP, Meandiffcrence -4.1 mmHg, 95% Cl -7.6 to -0.7,?=0.013), and body weight (Meandaffereoce-2.01 kg, 95% CI -2.92 to -1.1 0, P=O.O 13). There are also significant improvements in urinary albumin: creatinine ratio (Mdndiffcrcnce -0.45 mg/mmol, 95% CI -1.15 to < -0.001, P=O.O 19), square-root transformed eGFR (P=0.024), and the proportions of patients attaining HbAtc <7% (P<O.OOl) or SBP <140 mmHg (P=0.007. Suboptimally-controlled multi-ethnic Asians with T2DM showed substantial improvements in metabolic and renal parameters with dapagliflozin over a year.